Orientation relationship between TiFeH and TiFe phases in AB-type Ti-Fe-V-Ce hydrogen storage alloy - Lee, Seung-Yong; Ha, Taejun; Suh, Jin-Yoo; Kim, Dong-Ik; Lee, Young-Su; Shim, Jae-Hyeok (Elsevier BV, 2024)
The partially hydrogenated microstructure of an AB-type Ti-Fe-V-Ce hydrogen storage alloy was investigated using scanning electron microscopy (SEM) with electron backscatter diffraction (EBSD). For the first time, the formation of the orthorhombic beta-TiFeH phase was directly observed by using SEM-EBSD. Lamellar structures consisting of TiFeH and body-centered cubic TiFe phases with a (100)TiFeH||(100)TiFe habit-plane pair were observed. Pole figure analysis was performed to confirm the orientation relationship between the TiFeH and TiFe phases to be [011](100)TiFeH||[010](100)TiFe. The formation of TiFeH was characterized by simple lattice expansion with a short-range arrangement of H atoms and surface relief. In addition, unidirectional microcracks along the (100)TiFe planes were observed, presumably owing to the dehydrogenation of the TiFeH phase.